SAFETY POLICY STRATEGY: A KEY SUCCESS OF BUSINESS TRANSPORTATION - Wibawanti, Andjar Budi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This paper aims to find alternative policy strategies to improve seafarer safety behavior to reduce the potential for ship accidents. The activity uses literature studies supported by quantitative methods. Data is collected through relevant literature and key persons and analyzed using a logic model approach. The results show that one of the alternative strategic policies that can be considered to reduce seafarer accidents through improving seafarer safety behavior is a policy of improving the quality of resources through a special certification program for seafarers and supervisors. The safety certification program is designed for seafarers and supervisors with different materials, methods and instructors according to their respective job descriptions and lasts for 20 to 30 hours in five working days. These findings not only provide theoretical contributions to the development of transportation and public policy, but also have practical implications for shipping companies and the government.